Fulminant and Non-fulminant Clinical COVID-19 Myocarditis in the New York City Area in 2020 - Christopher Wong; Amtul Mansoor; Thomas McGinn (Ubiquity Press, 2022)
Background: COVID-19 myocarditis is becoming increasingly appreciated as a complication of COVID-19. There are significant hurdles to formal diagnosis with endomyocardial biopsy or cardiac MRI, whether by resource limitations, patient instability, or isolation precautions. Therefore, further exploratory analysis is needed to clinically define the characteristics and spectrum of severity of COVID-19 myocarditis. Objectives: The aim of this study was to describe the clinical course, echocardiographic, and laboratory testing across suspected fulminant and non-fulminant clinically defined COVID-19 myocarditis. Methods: In a cross-sectional observational study of 19 patients with clinically defined COVID-19 myocarditis, we report presenting symptoms, clinical course, laboratory findings, and echocardiographic results stratified by non-fulminant and fulminant myocarditis. Student t-test and univariate logistic regression are used to compare laboratory findings across fulminant and non-fulminant cases. Findings: Among 19 patients, there was no prior history of coronary artery disease, atrial fibrillation, or heart failure; 21.1% of patients died; and 78.9% of cases required supplemental oxygen. A significantly higher geometric mean D-dimer and ferritin were observed in patients with fulminant compared to non-fulminant suspected myocarditis. 26.3% of cases had pericardial effusions. 10 out of the 16 with available echocardiographic data had normal left ventricular systolic function. Conclusions: In this study, we provide a practical clinical depiction of patients with clinical COVID-19 myocarditis across fulminant and non-fulminant cases. Statistically significant elevations in inflammatory markers in fulminant versus non-fulminant cases generate hypotheses regarding the role of systemic inflammation. While cardiac MRI and endomyocardial biopsy may not be accessible at scale in low- and middle-income countries, the present study offers a clinical definition of COVID-19 myocarditis and accessible laboratory findings to define severity.